A Case Study of Neurocognitive Disorders/Dementia: 2015 Self-Learning Module - Martin Klapheke (Association of American Medical Colleges, 2015)
Abstract Introduction Liaison Committee on Medical Education standards mandate that medical schools identify clinical conditions students must experience during required clerkships. If a given clerkship site is unable to provide one or more of the required clinical experiences, it is permissible to provide an alternative clinical experience such as a simulated or case-based alternative that parallels the level of student involvement (e.g., observation vs. participation in management decisions) specified for the condition. This resource provides a case study of neurocognitive disorders/dementia. It was originally developed in 2012 and updated in 2015. Methods This resource is a self-contained module that can be viewed on any computer. The instructor/student can navigate at will through interactive quizzes, text, and imbedded video clips. The video clips demonstrate the evolution of a clinical case from presentation to follow-up over 5 years. The focus is on differential diagnosis and treatment planning, with intermittent self-assessment quizzes and references to American Psychiatric Association Practice Guidelines and other evidence-based literature. Results Student feedback has been generally positive. Satisfaction and confidence items for the 2012 version of this module were rated on 5-point Likert scales (1 = strongly disagree, 5 = strongly agree). Student surveys (N = 49) yielded mean ratings of 4.2-4.6 on items measuring general feedback about satisfaction with the module (relevant clinical content, video quality, audio quality, navigational ease of interactive features, value as an educational tool, effectiveness of quizzes, effectiveness of simulation exercise). Students' ratings of their own confidence about disorder-specific knowledge, diagnosis, and treatment were significantly higher postmodule compared to premodule (p < .001). Discussion Rather than providing a comprehensive didactic on neurocognitive disorders, this module is intended as a clinical application exercise after medical student completion of the recommended readings. An earlier version of the module has been utilized extensively since 2012 by faculty members of the Association of Directors of Medical Student Education in Psychiatry and others. This 2015 revision has been somewhat streamlined, quiz questions have been made more directly relevant to the presented case, and the module has been updated for DSM-5 terminology and other evidence-based literature.